2023
DOI: 10.3390/plants12040705
|View full text |Cite
|
Sign up to set email alerts
|

Palliating Salt Stress in Mustard through Plant-Growth-Promoting Rhizobacteria: Regulation of Secondary Metabolites, Osmolytes, Antioxidative Enzymes and Stress Ethylene

Abstract: The severity of salt stress is alarming for crop growth and production and it threatens food security. Strategies employed for the reduction in stress are not always eco-friendly or sustainable. Plant-growth-promoting rhizobacteria (PGPR) could provide an alternative sustainable stress reduction strategy owning to its role in various metabolic processes. In this study, we have used two strains of PGPR, Pseudomonas fluorescens (NAIMCC-B-00340) and Azotobacter chroococcum Beijerinck 1901 (MCC 2351), either singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Our results corroborate those of Gururani et al (2013), who discovered that PGPR-treated potato plants exposed to various stressors had increased activity of ROS-scavenging enzymes like APX, CAT, DHAR, GR, and SOD (salt, drought, and heavy metals). Khan et al (2023) also found that antioxidative enzymes (SOD, CAT, APX and GR) increased by 58.40, 25.65, 81.081 and 55.914%, respectively, over salt-treated plants through the application of Pseudomonas fluorescens. Additionally, salt-stressed okra plants treated with the PGPR Enterobacter sp.…”
Section: Discussionmentioning
confidence: 79%
“…Our results corroborate those of Gururani et al (2013), who discovered that PGPR-treated potato plants exposed to various stressors had increased activity of ROS-scavenging enzymes like APX, CAT, DHAR, GR, and SOD (salt, drought, and heavy metals). Khan et al (2023) also found that antioxidative enzymes (SOD, CAT, APX and GR) increased by 58.40, 25.65, 81.081 and 55.914%, respectively, over salt-treated plants through the application of Pseudomonas fluorescens. Additionally, salt-stressed okra plants treated with the PGPR Enterobacter sp.…”
Section: Discussionmentioning
confidence: 79%
“…In our investigation, P. fluorescens inoculation to mustard plants improved growth characteristics, such as RL, SL, plant height, DW, FW, leaf area, and leaf number, as also demonstrated in Pisum sativum by Sofy et al (2021). Overall, the enhancement of growth parameters in mustard plants in the presence of PGPR can be attributed to their plant growth promotion traits, such as IAA production, ACC deaminase activity, siderophore production, and solubilization of mineral nutrients (Khan et al, 2023). To boost plant growth under stressful conditions, PGPR secretes IAA, which results in an increase in root surface area and eventually improves nutrient absorption by the plant (Yasmin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…P. fluorescens strain (NAIMCC‐B‐00340) was obtained from the National Bureau of Agriculturally Important Microorganisms (NBAIM), Mau, India. This strain has previously been characterized for salinity tolerance (Khan et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations